The Role of Gen Z Students in Using Child – Friendly Digital Media in The Early Childhood Learning Process - Kasman, Apri (Edukasi, 2025)
Current educational patterns have very significant differences compared to past educational patterns, in the current generation z students tend to have the habit of using digitalization technology facilities in their daily activities. The role of Generation Z students is very necessary in utilizing child-friendly digital media in the learning process for young children. Of course, by paying attention to these child-friendly elements, Generation Z students will later be able to adapt to the needs of good learning media for young children at school. The aim of this research is to measure the extent of the role of generation z in the use of child-friendly media in the learning process in early childhood, of course with child-friendly media that suits the needs of generation z, this can later be developed and updated for further learning media. The research method in this study is to use descriptive qualitative research methods with interview techniques with respondents from gen z students of the early childhood education study program Padang Open University. The results of this research show that Generation Z students have a very good role in utilizing child-friendly digital media in the learning process for early childhood, by using appropriate child-friendly media for early childhood at school so that it has a very good impact on the development of children's intelligence. early age at school. The conclusion in the results of this research is that the role of Generation Z students has a significant influence in the use of child-friendly learning media for success in the learning process in early childhood.